On-line syntactic and semantic influences in reading revisited - Joel Pynte; Boris New; Alan Kennedy (Bern Open Publishing, 2009)
This study is a follow-up to Pynte, New and Kennedy (2008), Journal of Eye Movement Research . 2(1):4, 1-11. A new series of multiple regression analyses were conducted on the French part of the Dundee corpus, using a new set of syntactic and semantic predictors. In line with our prior study, quite different patterns of results were obtained for function and content words. We conclude that syntactic processing operations during reading mainly concern function words and are carried out ahead of semantic processing.